PAPR reduction in OFDM system using combined MCS and DHMT precoding - Mohd Danial Rozaini; Azlina Idris; Darmawaty Mohd Ali; Ezmin Abdullah (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
Orthogonal Frequency Division Multiplexing (OFDM) has become a preferable scheme for most high data rate wireless communication standards. However, the non-linear power amplifier effect experienced in the OFDM system has increases the peak-to-average power ratio (PAPR). This paper proposed a Median Codeword Shift (MCS) as a new solution to alleviate the effect of high PAPR. MCS takes advantage of the codeword structure and bit position changes through the manipulation of the codeword structure and permutation process to achieve a low PAPR value. Additionally, the enhanced version of MCS is also being proposed by merging MCS with the Discrete Hartley matrix transform (DHMT) precoding method to boost the PAPR reduction. Simulation results show that MCS is capable of minimizing PAPR of conventional OFDM with 24% improvement and at the same time outperform Selective Codeword Shift (SCS) with a 0.5 dB gap. A remarkable result was also achieved by MCS-DHMT with a 15.1% improvement without facing any bit error rate (BER) degradation.